Systematic analysis of beneficial reuse in unconventional oil and gas wastewater management - Robbins, Cristian A., author; Tong, Tiezheng, advisor; Carlson, Kenneth, advisor; Sharvelle, Sybil, committee member; Bandhauer, Todd, committee member (Colorado State University. Libraries, 2021)
Wastewater management within the unconventional oil and gas (UOG) sector has continued to grow in importance in correlation with the rising water footprint of hydraulic fracturing (HF). The predominant UOG wastewater management method in the U.S. is to dispose of the wastewater deep underground in geologically stable formations by deep-well injection (DWI). However, this method has been plagued with concerns such as induced seismicity and decreasing capacity for DWI in various UOG regions. Further, when the wastewater is disposed of via DWI this potential resource is no longer available for beneficial purposes. An alternative method to DWI is UOG wastewater treatment for beneficial reuse which repurposes the treated wastewater for end uses such as surface discharge. The main objective of this dissertation is to analyze key aspects of UOG wastewater management to include topics within technology, logistics, regulations, and economics in order to further facilitate increased wastewater treatment and beneficial reuse. At the core of UOG wastewater treatment and beneficial reuse is an advanced treatment technology that can effectively treat hypersaline and complex UOG wastewater. For my work, I focused on membrane distillation (MD), a hybrid thermal-membrane desalination process well-suited to treat UOG wastewater. An advantage of using MD is its inherent ability to use low grade waste heat as an energy source to power treatment. I investigated the availability and sufficiency of waste heat at the well-pad to power MD for on-site UOG wastewater treatment in Weld County, Colorado. Additionally, I also investigate the availability and sufficiency of natural gas at the well-pad to power MD. The analysis showed that well-pad waste heat is insufficient while natural gas is sufficient for long term on-site MD treatment. Next, the impact of logistics, specifically transportation distance and costs, was researched for DWI and centralized wastewater treatment (CWT) powered by natural gas compressor station (NGCS) waste heat. Unlike on-site treatment, wastewater needs to be transported for DWI or CWT and thus incurs a transportation cost. Using ArcGIS software, transportation distances and associated costs were analyzed for Weld County, Colorado at various scales. At the county scale, DWI was economically favored based on transportation, however, when the scale of operation was reduced for certain areas (i.e., county to local) the economic advantage shifted towards CWT. Additionally, NGCS waste heat for Weld County was quantified and the MD treatment demand was correlated to MD treatment capacity provided by NGCS waste heat for CWT. This analysis emphasized the importance of matching treatment demand with capacity provided by waste heat. Further, MD treatment of UOG wastewater has been constrained by surfactant-induced membrane pore wetting. Surfactants, commonly found in HF fluid, reduce the surface tension of membranes inducing wetting. We investigated two mitigation strategies, pretreatment via coagulation-adsorption and fabrication of omniphobic membranes. UOG wastewater sourced from the Denver-Julesburg Basin that induced exceptional wetting of a hydrophobic polyvinylidene fluoride membrane during MD treatment was used. Both strategies proved effective at mitigating surfactant-induced wetting, however, flux decline with the use of omniphobic membrane was unacceptable due to the effects of fouling thus hindering its viability. To better understand the surfactant composition in the UOG wastewater, ultrahigh pressure liquid chromatography (UHPLC) coupled with quadrupole time-of-flight mass spectrometry (QToF/MS) was implemented to identify surfactants in the UOG wastewater and qualify the effect of pretreatment in reducing surfactants. In the UOG wastewater, 192 surfactants were identified with 91 being reduced by full pretreatment. Finally, an in-depth perspective on the motivations and barriers to increased future treatment and beneficial reuse of UOG wastewater was provided. This analysis moved beyond technology, which receives the majority of research interest, to explore and better understand other non-treatment aspects. Four major barriers to beneficial reuse were identified which are technology, economics, regulations, and social. These barriers were clearly elucidated providing insight into ways to overcome them to facilitate increased beneficial reuse. A systems-level approach requiring broad collaborations across multiple disciplines pertaining to technology, policy, legislation, economics, and social science to shift UOG wastewater management towards treatment and beneficial reuse was proposed.
Keywords: unconventional oil and gas; wastewater management; membrane distillation; wastewater transportation; waste heat